CFD MODELING OF FUEL DROPLET EVAPORATION AND COMBUSTION PROCESSES IN GDI (GASOLINE DIRECT INJECTION) ENGINES - Mamadaliev Foziljon Abdullaevich (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Abstract   This  paper  presents  a  theoretical  CFD  (Computational  Fluid  Dynamics) modeling of the evaporation and combustion processes of fuel droplets in GDI-type internal combustion engines. The evaporation and combustion dynamics of the fuel droplet are characterized by spatial and temporal variations of temperature, pressure, and  concentration  fields.  Based  on  the  Navier–Stokes  equations  and  the  laws  of conservation of mass and energy, a comprehensive mathematical model of the system is developed. Using CFD methods, the temperature and pressure distributions within the  combustion  chamber  were  determined.  The  results  demonstrate  the  physical validity  of  the  model  and  provide  recommendations  for  optimizing  fuel  injection parameters to enhance combustion efficiency and reduce emissions.